Factors Influencing Interesting in Purchasing Bitcoin Digital Currency Insurance - Srithong, Apichai; Siripanich, Pachitjanut; Teerawanwiwat, Duanpen (Journal of Applied Statistics and Information Technology, 2022)
The objective of this research is to study the factors influencing the purchase of bitcoin digital currency insurance. The survey was conducted on 348 bitcoin investors through an online questionnaire. The results of the binary logistic regression analysis were categorized into four models according to four aspects of coverage. For robbery bitcoin insurance, the factor effected purchasing interest are insurance literacy, perceived risk of robbery and perceived risk of transaction-failure. For transaction-failure bitcoin insurance, they are insurance literacy, perceived risk of transaction-failure and experience regarding the delayed transaction. Insurance literacy and experience regarding the transaction-delayed are two factors effected purchasing interest on delay-in-transactions bitcoin insurance. And for all-coverage insurance, the significantly factors are insurance literacy, digital literacy, perceived risk of robbery and perceived risk of transaction-failure. In addition, bitcoin investors whom interested in purchasing bitcoin digital currency insurance are willing to pay premiums as follows: About 64% are willing to pay a premium of no more than 10,000 Baht per year for robbery coverage; 57% are willing to pay a premium of no more than 3,000 Baht per year for transaction-failure coverage; And 47% are willing to pay a premium of no more than 500 Baht per year for delay-in-transactions coverage. Lastly, there are 48.56% of bitcoin investors interested in purchasing the proposed bitcoin insurance policy with all coverage.